Touristic and territorial dimension of the ‘ruta norte’ of the way of Saint James in the Basque Country: different ideas, valuations and proposals for management of a multifaceted phenomenon - María Cruz Porcal Gonzalo; Adrián Díez Angulo; Josu Junguitu Iñiguez De Heredia (Boletín de la Asociación de Geógrafos Españoles)
Resumen